2015
DOI: 10.1158/1055-9965.epi-14-1125
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic Circulating Polyomavirus Antibody Levels and Risk of Non-Hodgkin Lymphoma

Abstract: Background: Three human polyomaviruses have been classified as probable (Merkel cell polyomavirus) or possible (BK and JC polyomaviruses) carcinogens, but few epidemiologic studies have examined associations between this growing class of viruses and risk of non-Hodgkin lymphoma (NHL).Methods: Associations between polyomavirus antibodies and NHL incidence were examined using data from the American Cancer Society Cancer Prevention Study-II. This nested case-control study included 279 NHL cases and 557 controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
7
2
Order By: Relevance
“…Data from Western cohorts have provided limited support for an etiologic association between serologic markers of these viruses and NHL . The four PyVs evaluated in our study all had seropositive rates >55%, slightly lower compared to rates reported in the CPS‐II conducted in the U.S . The only suggestion of an association between these viruses and NHL in our study was for the highest antibody levels of TSV among subjects in the SCS, all of whom are men.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Data from Western cohorts have provided limited support for an etiologic association between serologic markers of these viruses and NHL . The four PyVs evaluated in our study all had seropositive rates >55%, slightly lower compared to rates reported in the CPS‐II conducted in the U.S . The only suggestion of an association between these viruses and NHL in our study was for the highest antibody levels of TSV among subjects in the SCS, all of whom are men.…”
Section: Discussioncontrasting
confidence: 85%
“…This is the first population‐based prospective study to our knowledge to evaluate the relationship between human PyVs and NHL risk in an Asian population. Data from Western cohorts have provided limited support for an etiologic association between serologic markers of these viruses and NHL . The four PyVs evaluated in our study all had seropositive rates >55%, slightly lower compared to rates reported in the CPS‐II conducted in the U.S .…”
Section: Discussioncontrasting
confidence: 71%
“…However, the presence of a truncated LT-Ag MCPyV sequence in the nucleus, a peculiarity of MCPyV in Merkel cell carcinoma cells, has been reported in highly purified CD19 + /CD5 + CLL cells (Haugg et al, 2011;Pantulu et al, 2010). Serology data are furthermore inconsistent; in a previous case-control study we identified an increased MCPyV seroprevalence in CLL patients (Robles et al, 2012) whereas in a recent paper a decreased risk was observed (Teras et al, 2015), although none of them significant. The latter paper also observed null associations for seven additional polyomaviruses and subsequent risk of CLL, although potential concerns in sample size were raised.…”
Section: Received 9 January 2015mentioning
confidence: 62%
“…This increases the sensitivity and in comparison with conventional screening ELISA increases the specificity of antibody detection as it has been shown for HPV (Dillner, 2005; Waterboer et al , 2005), polyomaviruses (Kjaerheim et al , 2007) and Helicobacter pylori (Michel et al , 2009). The protein antigens used in the assay for our analysis have been shown to allow very sensitive and virus-type-specific antibody detection (Waterboer et al , 2005; Kjaerheim et al , 2007; Paulson et al , 2010; Liang et al , 2012; Teras et al , 2015). Moreover, there is ample evidence supporting the use of serological markers in detection of polyomaviruses.…”
Section: Discussionmentioning
confidence: 99%